2021
DOI: 10.1021/acs.jafc.1c05246
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorescent Probes for the Sensitive Determination of Glyphosate in Food and Environmental Samples

Abstract: In this paper, a dual-functional probe, 2-(benzothiazol)-4-(3-hydroxy-4-methylphenyl) imino phenol (BHMH), was synthesized and characterized for the simultaneous detection of Cu2+ and Fe3+ in dimethyl sulfoxide/4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (DMSO/HEPES) (1:4, v/v, pH = 6.0). The limits of detections (LODs) for Cu2+ and Fe3+ were 9.05 and 48 nM, respectively. Based on the competitive coordination, the complex BHMH-Cu 2+ /Fe 3+ exhibited good sensitivity and selectivity for glyphosate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…S5, ESI†). 22 Interestingly, signals for the protons present near bispicolyl nitrogens diminished completely during the interaction, indicating their close proximity to the Cu 2+ ion. However, when glyphosate (1 equiv.)…”
Section: Resultsmentioning
confidence: 97%
“…S5, ESI†). 22 Interestingly, signals for the protons present near bispicolyl nitrogens diminished completely during the interaction, indicating their close proximity to the Cu 2+ ion. However, when glyphosate (1 equiv.)…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the N-CQDs released Fe 3+ and restored its fluorescence intensity. 44 The mechanism of the sensing and detection procedure are shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the LUMO energy levels of isoxaflutole and mesotrione were lower than those of other pesticides (glyphosate, oxyfluorfen, pyrazoxyfen and cypermethrin), indicating that the electron affinities of isoxaflutole with the -CF 3 electron-withdrawing group and mesotrione with the -NO 2 electron-withdrawing group were relatively higher than those of other pesticides. Meanwhile, their LUMO energy levels were between the HOMO and LUMO energy levels of MMN , which could cause the transition of electrons from the LUMO orbital of MMN to the LUMO orbitals of isoxaflutole and mesotrione in the excited state [ 32 , 33 , 34 , 35 , 36 , 37 ]. The transition of electrons from the LUMO orbital of MMN in the excited state to the LUMO of isoxaflutole prevented the electrons from returning to the HOMO orbital of MMN , leading to the phenomenon of fluorescence quenching in the recognition of isoxaflutole.…”
Section: Resultsmentioning
confidence: 99%